Pengaruh Karakteristik Individu, Karakteristik Pekerjaan Dan Karakteristik Organisasi Terhadap Kepuasan Kerja Pegawai (Studi Kasus Pada Kantor Kecamatan Wera, Kabupaten Bima, Provinsi NTB) - Dwi Apriwanti; Mohammad Rizal; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect of individual characteristics, job caharacteristics and organizational characteristics on the employee job satisfaction variable in the case study at the Wera District Office, Bima Regency. The sample used was all employees of the Wera District Office, Bima Regency, as many 70 respondent. Data collection methods used in this study were questiooaires and interviews.Based on the results of this study it is know that individual characteristics, job characteristics and organizational characteristics have a simultaneous influence on the variable of job satisfaction of employees at the Wera District Office, Bima Regency. Individual characteristics have a significant influence on the variable of job satisfaction of employees at the Wera District Office, Bima Regency. Job characteristics have a significant nfluence on the variable of job satisfaction of employees at the Wera District Office, Bima Regency. Organizational characteristics have no partial effect on the variable of job satisfaction of employees at the Wera District Office, Bima Regency. Keywords: Individual Characteristics, Job Characteristics, Organizational Characteristics And Job Satisfaction.